A216 PREDICTING DIFFICULT CASES IN POEM (PER-ORAL ENDOSCOPIC MYOTOMY) PROCEDURES. (1st March 2018) - Jowhari, F; Inoue, H; Ikeda, H; Onimaru, M; Bechara, R
Abstract: Background: POEM (per-oral endoscopic myotomy) is emerging as the new endoscopic standard for treating patients with achalasia. Originating from Japan, POEM is now performed at many tertiary care centers in North America. Hitherto, data from institutions regarding the safety & efficacy of the procedure has shown promising results. To ensure that the procedure is seamless, identifying challenging cases ahead of time would allow for better resource allocation & to plan accordingly. Aims: To identify if certain pre-procedural factors are associated with intra-procedural factors or post-procedural complications, to ultimately formulate a POEM difficulty score to allow endoscopists to predict difficult cases ahead of time. Methods: 51 POEM procedures performed for achalasia at a tertiary care centre in Japan were analyzed in the study. Most procedures were performed by advanced-therapeutics trainees with close proctoring by experienced endoscopists. Various pre-determined pre-procedural factors (age, sex, achalasia type, duration of symptoms, Eckardt score, morphology & prior treatments); intra-procedural factors (tunnel distention, submucosal fibrosis, abnormal contractions, submucosal oozing, orientation, length of myotomy, procedure time, number of clips used & intra-procedural adverse events) & post-procedural data points were collected & analyzed. A preliminary POEM difficulty score (out of 10) was formulated with each component worth 2 points (tunnel distention, submucosal fibrosis, abnormal contractions, submucosal oozing, orientation). Analyses were performed using chi-square tests for categorical data & T-tests/ANOVAs/Spearmans correlations for continuous data. Results: The mean age was 44.3 ± 15.5 yrs & mean duration of symptoms 8.1 ± 9.9 yrs. Mean Eckardt score was 6.7 ± 2.2. Six patients (11.8%) had an intra-procedural event & 3 (5.9%) had an in-hospital adverse event. In the univariate analyses, the POEM difficulty score did not correlate with the occurrence of an intra-procedural event (p=0.203) or post procedure complications (p=0.80). Factors that correlated with the POEM difficulty score included morphology (S1/S2 vs. NS-D or NS-ND, p=0.006), prior treatments (pneumatic dilation vs. none, p=0.028) & age (p=0.030). A multivariate regression analysis was also conducted with variables removed sequentially, and even though trends were seen with some variables, type of achalasia was the only variable that maintained significance (p=0.048). Conclusions: Based on this study, there are indications that procedures involving older patients; S1/S2 morphology; type of achalasia (Type 1); and those with prior treatments may be more difficult overall. Further validation of these results as well as the POEM difficulty score is needed as our study was limited by smaller numbers, minimal adverse events, more trainee involvement, and less challenging procedures overall. Funding Agencies: None